2007
DOI: 10.1007/s00439-007-0448-6
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization: can genetic epidemiology help redress the failures of observational epidemiology?

Abstract: Establishing causal relationships between environmental exposures and common diseases is beset with problems of unresolved confounding, reverse causation and selection bias that may result in spurious inferences. Mendelian randomization, in which a functional genetic variant acts as a proxy for an environmental exposure, provides a means of overcoming these problems as the inheritance of genetic variants is independent of-that is randomized with respect to-the inheritance of other traits, according to Mendel's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
278
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 340 publications
(283 citation statements)
references
References 131 publications
4
278
0
1
Order By: Relevance
“…Furthermore, common variations in genes with known biological effects have been favored as a mean to test causality of disease mechanisms in observational studies 22. The present study extends earlier observations of a relationship between frontostriatally based cognitive functions and genes associated with dopamine transmission and is, to our knowledge, the first to demonstrate the DRD2 957 T/T genotype as a risk factor for PDD.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, common variations in genes with known biological effects have been favored as a mean to test causality of disease mechanisms in observational studies 22. The present study extends earlier observations of a relationship between frontostriatally based cognitive functions and genes associated with dopamine transmission and is, to our knowledge, the first to demonstrate the DRD2 957 T/T genotype as a risk factor for PDD.…”
Section: Discussionsupporting
confidence: 81%
“…A technique called Mendelian randomization is increasingly being used to determine causality in such situations. 54 In this technique, one selects a functional variant that is associated with an increased level of the marker in question, and determines whether it is also associated with an increased risk of the phenotype, in this case lacunar stroke. This approach has been used successfully in many cardiovascular diseases; for example, it has shown that elevated levels of C-reactive protein in patients with cardiovascular disease are likely to be secondary to atherosclerosis rather than having a causal role in disease pathogenesis.…”
Section: Insights Into Stroke Pathophysiologymentioning
confidence: 99%
“…The epigenotype, in contrast, is tissue and cell-type specific and may vary over time as a function of environmental exposure, aging, and random processes (48,60,172,173). Analysis of epigenetic data, therefore, cannot rely upon the assumptions of Mendelian randomization (174,175), which is predicated on the random assortment of genes transmitted from parents to offspring during gamete formation before disease onset. Associations between genotype and disease are therefore not usually biased because of reverse causation or confounding, unless linkage disequilibrium, pleiotropy, genetic heterogeneity, or population stratification are involved (174).…”
Section: Genetic and Epigenetic Analysismentioning
confidence: 99%